Transcriptome profiles of sunflower reveal the potential role of microsatellites in gene expression divergence. Issue 5 (8th March 2018) - Ranathunge, Chathurani; Wheeler, Gregory L.; Chimahusky, Melody E.; Kennedy, Meaghan M.; Morrison, Jesse I.; Baldwin, Brian S.; Perkins, Andy D.; Welch, Mark E.
Abstract: The mechanisms by which natural populations generate adaptive genetic variation are not well understood. Some studies propose that microsatellites can function as drivers of adaptive variation. Here, we tested a potentially adaptive role for transcribed microsatellites with natural populations of the common sunflower ( Helianthus annuus L.) by assessing the enrichment of microsatellites in genes that show expression divergence across latitudes. Seeds collected from six populations at two distinct latitudes in Kansas and Oklahoma were planted and grown in a common garden. Morphological measurements from the common garden demonstrated that phenotypic variation among populations is largely explained by underlying genetic variation. An RNA‐Seq experiment was conducted with 96 of the individuals grown in the common garden and differentially expressed (DE) transcripts between the two latitudes were identified. A total number of 825 DE transcripts were identified. DE transcripts and nondifferentially expressed (NDE) transcripts were then scanned for microsatellites. The abundance of different motif lengths and types in both groups were estimated. Our results indicate that DE transcripts are significantly enriched with mononucleotide repeats and significantly depauperate in trinucleotide repeats. Further, the standardized mononucleotide repeat motif A and dinucleotide repeat motif AG were significantly enriched within DE transcripts while motif types, C, AT, ACC and AAC in DE transcripts, are significantly differentiated in microsatellite tract length between the two latitudes. The tract length differentiation at specific microsatellite motif types across latitudes and their enrichment within DE transcripts indicate a potential functional role for transcribed microsatellites in gene expression divergence in sunflower.